2016
DOI: 10.3390/ijerph13111093
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Predicted 10-Year Atherosclerotic Cardiovascular Risk Using the Pooled Cohort Equations in U.S. Hypertensive Adults

Abstract: This study was to evaluate the association of urine arsenic with predicted 10-year atherosclerotic cardiovascular disease (ASCVD) risk in U.S. adults with hypertension. Cross-sectional analysis was conducted in 1570 hypertensive adults aged 40–79 years in the 2003–2012 National Health and Nutrition Examination Survey (NHANES) with determinations of urine arsenic. Predicted 10-year ASCVD risk was estimated by the Pooled Cohort Equations, developed by the American College of Cardiology/American Heart Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The full text of studies which was regarded as potentially eligible was then assessed and further excluded if they were (a) not related with dietary As exposure or not for the general population; (b) no available relative risk (risk ratios, odds ratios) and measures of variability of different types of CVD were mentioned; or c) no categorical As exposure (at least three categories) was used ( Figure S1). The methodological quality of the studies was also assessed and those with missing data on, or incomplete definitions of, the study design, population, exposure condition, or outcome variables were excluded [42][43][44][45][46][47][48][49]. Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51].…”
Section: Data Sourcesmentioning
confidence: 99%
“…The full text of studies which was regarded as potentially eligible was then assessed and further excluded if they were (a) not related with dietary As exposure or not for the general population; (b) no available relative risk (risk ratios, odds ratios) and measures of variability of different types of CVD were mentioned; or c) no categorical As exposure (at least three categories) was used ( Figure S1). The methodological quality of the studies was also assessed and those with missing data on, or incomplete definitions of, the study design, population, exposure condition, or outcome variables were excluded [42][43][44][45][46][47][48][49]. Furthermore, as it is difficult to convert plasma As to water As, we excluded two studies which could only provide plasma As concentration to lower the bias of exposure assessment [50,51].…”
Section: Data Sourcesmentioning
confidence: 99%
“…Stratification according to BP status is important to gain insight into the cardiovascular risk profile of hypertensive patients, which is directly related to arsenic exposure. 64 However, the rates of overweight and obesity, conditions independently related to cardiac growth, 65 were high (27.9% and 46.3%, respectively); nevertheless, interaction analysis showed no effect modification by BMI status. Circadian variation of BP levels, as well as changes in BP treatment and compliance, could have an impact on measures of cardiac geometry but were not available for the present study.…”
Section: Discussionmentioning
confidence: 92%
“…For example, several papers in our literature review discussed the use of urinary metal exposures as a limitation (notably one that is also present in our pilot analysis) because urinary exposures do not necessarily reflect total lifetime exposure, or even average exposure over an extended time period depending on the metal of interest and renal functioning. 29,39,40 Our systematic literature review suggested several mechanisms through which exposure to individual metals could potentially affect cardiometabolic health outcomes; however, future work is needed to understand how metals may interact physically and/or chemically to affect health. For individual metals, much of the literature focuses on how arsenic may be associated with cardiometabolic health through mechanisms mediated by epigenetic changes, 29 and through associations with immune function, endothelial dysfunction, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several papers in our literature review discussed the use of urinary metal exposures as a limitation (notably one that is also present in our pilot analysis) because urinary exposures do not necessarily reflect total lifetime exposure, or even average exposure over an extended time period depending on the metal of interest and renal functioning. 29, 39, 40…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation